Global Stability for a Three-Species Food Chain Model in a Patchy Environment - Hongli Li; Yaolin Jiang; Long Zhang; Zhidong Teng (Journal of Applied Mathematics)
We investigate a three-species food chain model in a patchy environment where prey species, mid-level predator species, and top predator species can disperse among n different patches (n≥2). By using the method of constructing Lyapunov functions based on graph-theoretical approach for coupled systems, we derive sufficient conditions under which the positive equilibrium of this model is unique and globally asymptotically stable if it exists.